The effect of kappa carrageenan on physical and textural properties as well as sensory parameters on plant protein mixture-based nuggets - Sakamut, Phatthira; Jindasuay, Warissara; Klamchuen, Yamonpat (Food and Applied Bioscience Journal, 2023)
This study investigated the effect of kappa carrageenan on physical properties (cooking loss and color), texture profile analysis (TPA) and sensory evaluation of 2 recipes plant based nuggets namely soy and pea protein mixture-based nuggets (SPPN) and gluten-free plant protein mixture-based nuggets (GFPN) The ratio of soy protein to pea protein was carried out at three levels: 25:75, 50:50 and 75:25. TPA parameters including hardness, cohesiveness, and chewiness were increased as soy protein content increased (P<0.05), but cooking loss decreased (p > 0.05). SPPN at all levels showed different color values from chicken nuggets. SPPN at a 50:50 level was chosen to produce GFPN based on the highest sensory evaluation score. Three levels of kappa carrageenan were added (1%, 3% and 5% by weight) to GFPN and compared with SPPN without kappa carrageenan. The increment of kappa carrageenan levels increased hardness and chewiness (P<0.05), but decreased springiness, cohesiveness and cooking loss (P>0.05). No significant color difference was found between GFPN with 1% kappa carrageenan and the control sample. GFPN with 5% kappa carrageenan was chosen because exhibited the highest ratings for appearance, aroma, texture and overall liking scores (P<0.05). Comparing GFPN with 5% kappa carrageenan to chicken nuggets, crude fiber, fat, protein, carbohydrates and energy were decreased 22%, 15.03%, 4.75%, 17.34%, and 11.81%, respectively whilst increased 47.19% and 6.26, respectively. The combination of carrageenan and a plant-protein mixture (without gluten-free) shows the possibility of developing nuggets.